Serving up health: How phytochemicals transform food into medicine in the battle against cancer - Sharma, Eshita; Tewari, Manju; Sati, Priyanka; Sharma, Isha; Attri, Dharam Chand; Rana, Supriyanka; Aldahish, Afaf Ahmed; Calina, Daniela; Dhyani, Praveen; Sharifi‐Rad, Javad; Cho, William C. (Food frontiers, 2024)
The escalating global cancer burden underscores the urgent need for more effective therapeutic strategies. Phytochemicals, naturally occurring compounds in plants, have garnered attention for their potential in cancer chemoprevention and chemotherapy. Their ability to modulate molecular mechanisms and influence cell signaling pathways offers a promising avenue for cancer management. This review aims to synthesize current knowledge on phytochemicals’ chemopreventive and chemotherapeutic potential, focusing on their molecular mechanisms of action and impacts on cell signaling pathways involved in cancer. A systematic literature search was conducted across major databases, including PubMed/Medline, Web of Science, Scopus, and Google Scholar. The search strategy uses Medical Subject Headings (MeSH) and free‐text terms using Boolean operators to capture relevant studies. Inclusion criteria targeted original research and reviews on the effects of phytochemicals in cancer, with a specific focus on molecular mechanisms. Phytochemicals, including flavonoids, polyphenols, and terpenoids, demonstrated significant anticancer properties by inducing cell cycle arrest, apoptosis, and autophagy. They modulate critical cell signaling pathways, such as cyclooxygenase‐2, nuclear factor kappa B, and various growth factor‐related pathways, and rectify epigenetic alterations, contributing to their chemopreventive and therapeutic effects. Phytochemicals represent a valuable resource for developing novel cancer prevention and treatment strategies; their actions on molecular mechanisms and cell signaling pathways underscore their potential in cancer prevention and combat. Further research is warranted to translate these findings into clinical applications, optimizing phytochemical‐based interventions for cancer management. Phytochemicals from fruits and vegetables exhibit anticancer activity through multiple mechanisms, with the Nrf2 pathway being one of the most important. Under oxidative stress, Nrf2 is released from Keap1, translocates to the nucleus, and activates antioxidant response elements (ARE), leading to increased antioxidant enzyme expression. This process reduces reactive oxygen species (ROS), thereby inhibiting cancer cell proliferation and metastasis.